FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK PADA REMAJA LAKI-LAKI - Nur Safitri, Anita; Wahyuni, Tri; Pratama, Kharisma (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Smoking behavior among male adolescents remains a major public health issue in Indonesia. Adolescence is a critical developmental stage where individuals are vulnerable to social, familial, and media influences that can initiate early smoking habits. Objective: This study aimed to identify the factors influencing smoking behavior among male adolescents in Dusun Keramat 1. Methods: This research employed an analytical observational design with a cross-sectional approach. The population consisted of 850 male adolescents, with 89 respondents selected using a purposive sampling technique. Data were collected using a structured questionnaire covering parental influence, peer influence, personality, and advertising exposure. Descriptive analysis was used to determine the dominant factors influencing smoking behavior. Results: The findings revealed that most respondents were 17 years old (18%) and categorized as light smokers (56.2%), with the majority beginning to smoke during junior high school (55.1%). The most influential factors on smoking behavior were parental influence (70.8%), peer influence (66.3%), cigarette advertising (61.8%), and personality (59.6%). Conclusion: Smoking behavior among male adolescents is shaped by a combination of family, social, and media factors. Preventive efforts should focus on enhancing parental involvement and school-based health education to promote positive role modeling and reduce smoking initiation among youth